Thickness effects on the high-frequency characteristics of as-deposited Co-Ni-Fe and Co-Ni-Fe-N soft magnetic thin films - Kim, YM; Choi, D; Kim, KH; Kim, J; Han, SH; Kim, HJ (ELSEVIER SCIENCE BV, 2002)
The thickness effects on the high-frequency characteristics of as-deposited Co-Ni-Fe and Co-Ni-Fe-N soft magnetic thin films have been investigated in the range of 0.01-1.0 mum, The B-s of both these films decrease with a decrease in the film thickness below 0.5 mum, which is due to the decrease in the Fe content in the film composition whereas, the coercivity (H-c) of these films in creases largely with the decrease in the film thickness, It is interpreted to be the result of the change in the film composition and surface roughness. The electrical resistivity (p) also increases with decrease in the film thickness, especially below 0.1 mum. The effective permeability of a Co-Ni-Fe film is maintained up to 700 MHz below 0.05 mum thickness. and that of Co-Ni-Fe-N thin films up to above 700 M Hz below 0.1 mum thickness. A Co-Ni-Fe-N film exhibits better high-frequency characteristics than a Co-Ni-Fe film, which results from the difference in the electrical resistivity. These films are formed in an amorphous phase during the initial growth stage and it gradually changes to crystalline structure as the film thickness increases. (C) 2002 Elsevier Science B.V. All rights reserved.